A new concept for bisphosphonate therapy: a rationale for the development of monthly oral dosing of ibandronate. - Reginster, J; Felsenberg, D; Cooper, C; Stakkestad, J; Miller, P; Kendler, D; Adami, S; McClung, MR; Bolognese, M; Civitelli, R; Dumont, E; Bonvoisin, B; et al. (2006)
Oral daily and weekly bisphosphonates represent the current mainstay of treatment for postmenopausal osteoporosis (PMO). However, the inconvenience of frequent dosing is known to negatively affect adherence to therapy in the long term. This has prompted the development of convenient oral bisphosphonate regimens that feature simple, less frequent dosing schedules. Such regimens require high potency agents, which can be given at low effective doses and that also have good tolerability. Ibandronate is a potent, nitrogen-containing bisphosphonate with proven efficacy when given intermittently to estrogen-depleted beagle dogs, rats and cynomolgus monkeys. Clinically, a pivotal prospective study has established that oral ibandronate has significant vertebral fracture efficacy in PMO, whether given daily (2.5 mg) or intermittently (20 mg every other day for 12 doses every 3 months; extended between-dose interval>2 months). Both oral regimens were well tolerated, which is noteworthy as patients with a history of gastrointestinal (GI) disturbance were not specifically excluded. As a result of these findings, a large, multinational, randomized, double-blind study (Monthly Oral iBandronate In LadiEs: MOBILE) is currently exploring the non-inferiority of once-monthly oral ibandronate (100 or 150 mg) to the oral daily ibandronate (2.5 mg) regimen with proven anti-fracture efficacy, in terms of lumbar spine bone mineral density (BMD) change. As with the trials investigating the weekly administration of other bisphosphonates, vertebral fracture efficacy will be inferred if the study demonstrates the non-inferiority of once-monthly ibandronate to the proven oral daily regimen in terms of spinal BMD change. The availability of this once-monthly ibandronate regimen is expected to offer benefits in terms of convenience (by having to follow dosing recommendations once a month vs. once daily or weekly) and potentially tolerability (by reducing the potential for upper GI irritation that can result from frequent, repeated exposure). Greater convenience and tolerability may enhance the therapy adherence and, hence, improve long-term therapeutic outcomes in PMO.